MODEL SISTEM INFORMASI GEOGRAFIS UNTUK ESTIMASI KOEFISIEN ALIRAN DAN HUBUNGANNYA DENGAN TUTUPAN LAHAN DI DAS RIAM KANAN PROVINSI KALIMANTAN SELATAN - Abdur Rahman (Bumi Lestari Journal of Environment, 2013)
AbstractSimple approach to estimate watershed runoff coefficient value is needed model to forecastproblem of demage and watershed and hydrology data problem. Have happened degradationof energy support in Riam Kanan Sub Watershed which critical of landcover impact.This research aims are to estimation surface runoff and distribution in Watershed of RiamKanan based on Landsat7 ETM+ Imagery. The Research found that the accuracy testusing Landsat7 ETM+ image aqual to 87 %, indicates that it has a high accuration todetect of landcover. The results of overlay raster data from landcover parameter was obtainedby distribution pattern of runoff coefficient dominated normal class aqual to 61,94 percent,low class aqual to 0,53 percent and high class aqual to 78,14 percent distributed at upstream and middle of Riam Kanan Sub Watershed. Result of statistical test indicated thatresult of C estimation do not different with result of C actual at significant 95% withenough, mean accuration equal to 78,14 %.